Spade Leaf Extract Phytosome Modulates Krox-20, Neuregulinـ1, Phospholipids, and Cognitive Function of Traumatic Brain Injury Model in Rats - Alif Fariz Jazmi; Putri Fitri Alfiantya; Sitti Ayu Hemas Nurarifah; Erlin Aditia Purmitasari; Lilin Andreas Vitania; Wibi Riawan (Indonesian Society for Cancer Chemoprevention, 2015)
Traumatic brain injury (TBI) is a disorder of the central nervous system due to head trauma. TBI can damage nerve membrane phospholipids and decrease protein synthesis of neuregulin-1 (NRG-1) because of the transcription factor Krox-20. These conditions cause the lowering in nerve re-myelination which contribute to the decline of cognitive function. In Indonesia, citicoline is a neuroprotective drug that widely used to repair and prevent further damage of the nerve cells membrane caused by trauma. Spade leaf (Centella asiatica) extract phytosome (SEP) is a model of drug delivery system which expected to enhance the therapeutic effects as neuroprotective drug. This study aims to demonstrate and compare the effectiveness from SEP and citicoline as a neuroprotective characterized by increasing the activation of Krox-20, the expression of NRG-1, the distribution of phospholipids, and the improvement of cognitive levels on TBI-induced rats. Rats were divided into 5 groups namely: control (-); control (+); treatment with SEP 90mg/kgBW; citicoline 250mg/kgBW, and SEP in combination with citicoline. Krox-20, NRG-1, and phospholipids expression were measured by immunohistochemical assay, while cognitive function were assessed with the Morris Water Maze test. According to ANOVA test results, it was showed that SEP improved the nerve cells through the activation of Krox-20, NRG-1 expression, and distribution of phospholipids significantly (p <0.05). Based on Morris Water Maze test, SEP also improved the cognitive function in TBI-induced rats. Thus, it can be concluded that spade leaf extract phytosome combined with citicoline increase a higher phospholipids distribution and give the fastest time in the cognitive tests compared with of spade leaf extract phytosome and citicoline alone.Keywords : NRG-1, Krox-20, phospholipids, phytosome, Centella asiatica.